Factors of psychiatric morbidity during perinatal period (Bangladesh Journal of Psychiatry, 2018)
The presence of psychiatric disorders during perinatal period imposes negative and long-term effect on maternal health and child development as well as normal family environment. The purpose of our study was to investigate the socio-demographic factors associated with psychiatric morbidity during perinatal period. It was a descriptive cross-sectional study conducted among purposively selected 197 perinatal women attending the Obstetrics & Gynaecology Outpatient Department (OPD) of Bangabandhu Sheikh Mujib Medical University and Dhaka Medical College Hospital, Dhaka from August 2012 to July 2013. Data were collected through face-to-face interview by administering a semistructured questionnaire, containing socio-demographic and other variables and translated Bangla version of Structured Clinical Interview for DSM-IV Axis-I Disorders – Clinician Version (SCID-CV). Majority (79.7%) of the women were included in the age group of 20-34 years. The mean (±SD) age of the respondents were calculated as 24.60 (±4.88) years. Rural habitat was predominant (53.6%). A good number (5.1%) of respondents with psychiatric disorders had positive family history of psychiatric illness which was found statistically significant. Majority (7.6%) of the respondents with psychiatric disorders had previous history of psychiatric illness. Women in perinatal period with the risk factors for developing psychiatric disorders need proper psychiatric evaluation to prevent and treat perinatal mental illness.Bang J Psychiatry December 2015; 29(2): 53-58